Full-thickness chest wall resection for malignant chest wall tumors and postoperative problems - Asanuma, Kunihiro; Tsujii, Masaya; Hagi, Tomohito; Nakamura, Tomoki; Kita, Kouji; Shimamoto, Akira; Kataoka, Takeshi; Takao, Motoshi; Sudo, Akihiro (Frontiers in Oncology, 2023)
Background: Chest wall malignant tumor (including primary and metastatic lesions) is rare, representing less than 5% of all thoracic malignancies. Local control of chest wall malignancies requires wide resection with tumor-free margins. These requirements increase the risk of thoracic cavity failure and subsequent pulmonary failure. The restoration strategy for chest wall defects comprises chest wall reconstruction and soft-tissue coverage. Various reconstruction methods have been used, but both evidence and guidelines for chest wall reconstruction remain lacking. The purposes of this study were to collate our institutional experience, evaluate the outcomes of full-thickness chest wall resection and reconstruction for patients with chest wall malignant tumor, and identify problems in current practice for chest wall reconstruction with a focus on local control, complications, pulmonary function and scoliosis. Methods: Participants comprised 30 patients with full-thickness chest wall malignant tumor who underwent chest wall resection and reconstruction between 1997 and 2021 in Mie University Hospital. All patients underwent chest wall resection of primary, recurrent or metastatic malignant tumors. A retrospective review was conducted for 32 operations. Results: Recurrence was observed after 5 operations. Total 5-year recurrence-free survival (RFS) rate was 79.3%. Diameter ≥5 cm was significantly associated with poor RFS. The postoperative complication rate was 18.8%. Flail chest was observed with resection of ≥3 ribs in anterior and lateral resections or with sternum resection without polyethylene methylmethacrylate reconstruction. Postoperative EFV1.0% did not show any significant decrease. Postoperative %VC decreased significantly with resection of ≥4 ribs or an area of >70 cm2. Postoperative scoliosis was observed in 8 of 28 patients. Posterior resection was associated with a high prevalence of scoliosis (88.9%). Conclusions: With chest wall reconstruction, risks of pulmonary impairment, flail chest and scoliosis were significantly increased. New strategies including indications for rigid reconstruction are needed to improve the outcomes of chest wall reconstruction.